Improving cost estimation in construction projects. Issue 1 (2nd January 2023) - Sayed, Mohamed; Abdel-Hamid, Mohamed; El-Dash, Karim
Abstract: The accurate cost estimate is one of the success keys to construction projects. The influence of inaccurate cost estimation on construction projects is critical. There is no consensus among researchers about the most important factors influencing the cost estimate accuracy. The study's objective is to get an accurate cost estimate because the precise cost estimate keeps all parties focused on delivering the project within the budget. This objective is achieved by collecting the influential factors from the literature review and creating a powerful arithmetical model of cost estimation. Twenty-nine factors were collected by reviewing many researches. A questionnaire was prepared and then was examined by fourteen project managers. Pareto technique was conducted to get the foremost influential factors. Based on the Pareto technique, the 29 factors were reduced to nine. Then, a powerful arithmetical model was created in this study to get an accurate cost estimate. Finally, fourteen finished projects were selected to be case studies. The cost variance percentages were between 1% and 15% for each case study. By using the model, the estimated contract value of each case study was recalculated and, the cost variance percentages were between 0.5% and 0.8% for each case study.